SECURITY POLICY ANALYSIS: A STUDY OF THE BNPT'S DERADICALISATION POLICY TOWARDS FORMER TERRORISTS IN THE CITY OF MAKASSAR - Sukri; Nur Alamsyah Putra (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
This study aims to analyse the implementation of deradicalisation policies carried out by the National Counterterrorism Agency (BNPT) on former terrorist convicts in Makassar City. Using a qualitative approach and descriptive design, data was collected through in-depth interviews with key informants, including the BNPT team, former terrorist convicts, and other relevant institutions. The findings show that the BNPT's deradicalisation policy is implemented in three main stages, namely national insight, religious insight, moderation, and entrepreneurship. The entrepreneurship programme is at the core of this policy, with the aim of increasing the economic independence of ex-terrorists after their release from prison. In addition, this study found significant challenges in terms of coordination between the institutions involved, budget constraints, and social acceptance of the ex-terrorists. Nevertheless, the deradicalisation programme has succeeded in reducing the potential for ex-terrorists to re-engage in radicalisation, especially with the support of the local community. Based on these findings, it is recommended to strengthen regional regulations and improve coordination between relevant institutions in order to improve the effectiveness of deradicalisation policies in the future.